Network-based distributed mobility management for network mobility (2014)
Network Mobility (NEMO) Basic Support Protocol (NBSP) provides mobility supports for mobile networks. NBSP is an extension of Mobile IPv6 which employs a centralized mobility management approach. It relies on a static and centralized home agent for signaling management and data forwarding. All data traffic traverse a centralized home agent, which leads to suboptimal routing, high packet overhead and latency, especially in nested NEMO (i.e. when the mobile networks connect to one another to reach the infrastructure). In this paper, we develop a network-based distributed mobility management (DMM) scheme for non-nested and nested NEMO scenarios, with the goal of mitigating the aforementioned problems. Additionally, the proposed scheme improves the packet delivery and location update (i.e., binding update) costs. The paper discusses in detail the scheme's design, operation mechanism and the performance evaluation analysis. The numerical results of the proposed scheme show significant improvement in packet overhead and latency as well as binding update and packet delivery costs. © 2014 IEEE.